Media House Shape Sorter untuk Meningkatkan Pemahaman Geometri Anak Usia 5-6 Tahun: House Shape Sorter Media To Improve The Understanding Of Geometry For Children Aged 5-6 Years - Khikmah Novitasari; Rhamadhani Annisa (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
The use of media is very important in improving the understanding of geometry in early childhood. The purpose of this study was to determine the increase in understanding of geometry when using house shape sorter media, the feasibility of house shape sorter media and the effectiveness of house shape sorter media as a learning medium for understanding geometry. The research was conducted at ABA Labbaik Among Putro III Kindergarten. This research was conducted with a development method using the ADDIE model (analysis, design, development, implementation, evaluation) with a one group pre-test and post-test design and the subjects used were 18 children aged 5-6 years. The analysis technique used is using the T-test. The results showed that the significant value for the pre-test and post-test was known that the value of 0.009 <0.05 so that the conclusion was that there was an increase in the understanding of geometry of children aged 5-6 years in class B TK ABA Labbaik Among Putro III, after treatment using the media house shape sorter. ABSTRAKÂ  Penggunaan media sangat penting dalam meningkatkan pemahaman geometri pada anak usia dini. Tujuan penelitian ini untuk mengetahui peningkatan pemahaman geometri jika menggunakan media house shape sorter, kelayakan media house shape sorter dan efektivitas media house shape sorter sebagai media pembelajaran pemahaman geometri. Penelitian dilakukan di TK ABA Labbaik Among Putro III. Penelitian ini dilakukan dengan metode pengembangan menggunakan model ADDIE (analysis, design, development, implementasi, evaluasi) dengan rancangan one group pre-test and post-test design dan subjek yang digunakan 18 anak usia 5-6 tahun. Teknik analisis yang digunakan adalah menggunakan uji-T. Hasil penelitian menunjukkan bahwa nilai signifikan untuk pre-test dan post-test diketahui bahwa nilai 0,009<0,05 sehingga kesimpulannya adalah terdapat peningkatan pemahaman geometri anak usia 5-6 tahun kelompok kelas B TK ABA Labbaik Among Putro III, setelah dilakukan treatment menggunakan media house shape sorter.